Experimental investigation of the characteristics of dynamics of ship to ship collision [electronic resource] - Fahd Ezadee Jamaludin, 1985- author; Fakulti Kejuruteraan Mekanikal (2009)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Teknologi Marin)) - Universiti Teknologi Malaysia, 2009